The Changes in the Arab Policy of Turkey from 2002-2010 : With a special reference to the Turkish Policy towards Syria - Abdel Fattah, Shaimaa (AUC Knowledge Fountain, 2012)
After long decades of estrangement since the establishment of the republic, the Arab policy of the AK party manifested visible changes that broke up with the state establishment mindset by underlining a sort of rapprochement on the regional level. This study aims to identify and understand the political and economic aspects of the Turkish policy towards Arab countries by according specific attention to Syria that constitutes for the current Turkish leadership a prototype for the Turkish policy towards its neighbors notably Arab countries. By taking account of the context within which these changes in the policy formulation occurred, the power structure model presents the analytical tool that enabled this study to explain how the new elitist configuration that was bourgeoning since the 80's in the Turkish society reconsidered the formulation of the Turkish foreign policy tenets in light of the domestic and international conditions. In addition to the various literature dealing with the ruling elite socioeconomic structure and their evolution on the political scene in Turkey, the contributions provided by various respondents, addressed by a questionnaire, from the ruling party, the opposition, academic scholars and journalists about the current elite's cognitive map in terms of perceiving Arabs and addressing them highlighted different reasons for the changes in the Turkish Arab policy. By relying on the literature and the respondents' reactions, the Arab policy of Turkey since 2002 seemed to be controversial since it not only concretizes Turkey's national interests but also contributes to the empowerment of the its role as a regional actor that seeks a permanent presence and influence on the international level.